Effect of Pineapple Fruit Water (Ananascomosus (L). Merr) Bio-supplement on the Carcass and Final Weight of Commercial Broilers - Resha Adrian Eko Hartanto; Ragil Angga Prastiya; Trilas Sardjito; Sri Hidanah; Moh. Anam Al-Arif; Bodhi Agustono; Amung Logam Saputro; Nagia Musa Alghoul (The Indian Veterinary Journal, 2023)
A study was conducted to determine the effect of Pineapple Fruit Water (Ananascomosus (L). Merr) Bio-supplements (PFWB) as an alternative drinking water supplement for broilers to achieve the carcass and final weight. Lohman broilers were kept in stage cages were subjected to different treatments, namely, P0 (0% without PFWB), P1 (given 15% PFWB) and P2 (given 30% PFWB). The data on final weight and carcass weight were collected at35 days of age. The results indicate a significant difference (p<0.05) in both final weight and carcass weight for each treatment. The results indicated that the pineapple fruit water bio-supplements can serve as a viable and efficient alternative at 15% dosage in drinking water for commercial broilers.